Socioeducação no estado do paraná: os sentidos de um enunciado necessário - Cossetin, Márcia (2012)
This dissertation has the object of its analysis of socio-educational public policy. The overall goal is to Investigate and understand the constitution and Objectives of socio-educational, Announced in the State of Paraná in the Guiding Notebook "Social Practices-education" The research problem is: how is and what the goals of socio-educational state of Paraná, in the text of the Guiding Notebook "Social Practices-education"? To address the problem we Conducted archival research and literature on the historical constitution of assistance to children and youth at the national and at the state level and the such, we analyze the text Guiding Notebook “Social-education Practices” for understanding That this are the theoretical basis for the socio-educational and Proposed Objectives of the educational practices of this "new articulation." Thus the nature of the study is a survey of theoretical character that is based on literature review and document content. We Establish a dialogue with authors who have discussed the issue and assist us in understanding the meanings of utterances ideological and theoretical research. The method we adopt historical materialism, Thereby analyze the object in Conjunction with the historical setting of capitalist social relations That legitimate social regulation strategies. The considerations That we are That socio-educational, That the term has received recent notoriety in the social state of Paraná from the years of 2005/2006, is composed from the complex in Which They operate different policies, social, educational and criminal, is the constituted such a statement and the ideological sign that represents a specific view of the world. The socioeducational, although Considered distinct from education, allied himself with this wish by refocusing, re-educate adolescents in conflict with the law. The term "socio-educational" comes with new approaches in the assistance to adolescents in conflict with the law, yet converges with goals of previous legislation, with utterances produced the document called "Education: A treasure to discover", known as "Jacques Delors Report "with education and Associated speeches. The text Expressed in Guiding Notebook “Socialeducation Practices” presents the constitutive function of forming peaceful and participating subjects; highlights forms of social regulation Within the set, featuring more control over the individual mediated contemporarily by education or by its new denominations, when it comes to the ones who commit actions known as crimes, the Social-education.